Diet Quality and Survival in a Population-Based Bladder Cancer Study. (30th June 2022) - Leeming, Reno C.; Karagas, Margaret R.; Gilbert-Diamond, Diane; Emond, Jennifer A.; Zens, Michael S.; Schned, Alan R.; Seigne, John D.; Passarelli, Michael N.
Abstract: Nutrition may impact bladder cancer survival. We examined the association between diet quality and overall and bladder cancer-specific survival. Bladder cancer cases from a population-based study reported pre-diagnosis diet. Diet quality was assessed using the 2010 Alternate Healthy Eating Index (AHEI-2010). Vital status was ascertained from the National Death Index. Adjusted hazard ratios (HR) and 95% confidence intervals (CI) were estimated using proportional hazards and competing risks regression models. Overall AHEI-2010 adherence was not associated with overall or bladder cancer-specific survival among non-muscle invasive bladder cancer (NMIBC) cases (HR, 1.00; 95% CI, 0.98-1.01; HR, 1.00; 95% CI, 0.97-1.02) or muscle invasive bladder cancer (MIBC) cases (HR, 0.99; 95% CI, 0.96-1.03; HR, 1.01, 95% CI 0.97-1.06). AHEI-2010 sugar-sweetened beverages adherence was associated with poorer overall survival (HR, 1.04; 95% CI, 1.01-1.08) and AHEI-2010 sodium adherence was associated with better overall and bladder cancer-specific survival after NMIBC diagnosis (HR, 0.92, 95% CI, 0.85-1.00; HR, 0.82; 95% CI, 0.68-0.98). AHEI-2010 fruit adherence was associated with poorer overall and bladder cancer-specific survival after MIBC diagnosis (HR, 1.17; 95% CI, 1.02-1.33; HR, 1.26; 95% CI, 1.03-1.55). Consumption of sugar-sweetened beverages, sodium, and fruit, not overall AHEI-2010 adherence, may be associated with bladder cancer survival.